Reminder to resubmit the price offer for facade curtain wall and relative works, variation order #031 - Brac University; Brac University (Brac University, 2023)
This record consists of general correspondence regarding reminder to resubmit the price offer for facade curtain wall and relative works, variation order #031 of BRAC University new campus project.